The Influence of Leadership Style and Organizational Culture on Employee Performance Through Job Satisfaction Among Employees of The Inspectorate General of The Ministry of Manpower of the Republic of Indonesia - Amirulloh; Harry Indratjahyo; Muhammad Harri (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
The Inspectorate General of the Ministry of Manpower has a crucial role in shaping policies and programs within the employment sector. However, challenges related to employee job satisfaction adversely affect organizational effectiveness, leading to diminished motivation, lower engagement, and a focus on mere obligation rather than intrinsic motivation among employees. These persistent issues could have long-term detrimental effects on productivity, innovation, and the quality of public services. This study explores the roles of leadership and organizational culture as independent variables, with job satisfaction as a mediating variable and employee performance as the dependent variable. The analysis reveals that both leadership style and organizational culture positively influence job satisfaction, indicating that improved leadership and a strong organizational culture enhance employee satisfaction. However, organizational culture does not directly affect employee performance when considering job satisfaction. Ultimately, the findings emphasize the mediating role of job satisfaction in the relationship between leadership style and employee performance, while highlighting that organizational culture does not share this mediating impact.